1998
DOI: 10.1016/s0928-8244(98)00015-7
|View full text |Cite
|
Sign up to set email alerts
|

The Leishmania promastigote surface antigen-2 (PSA-2) is specifically recognised by Th1 cells in humans with naturally acquired immunity to L. major

Abstract: The promastigote surface antigen-2 (PSA-2) is a Leishmania parasite antigen, which can induce Th1-mediated protection against murine leishmaniasis when used as a vaccine. To evaluate PSA-2 as a human vaccine candidate the specific T-cell response to PSA-2 was characterised in individuals immune to cutaneous leishmaniasis. Peripheral blood mononuclear cells from Sudanese individuals with a past history of self-healing cutaneous leishmaniasis proliferated vigorously in response to PSA-2 isolated from Leishmania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This protein is involved in parasite attachment and invasion of host macrophages via interactions with the complement receptor 3 (CR3) (Kedzierski et al 2004). Previous studies indicated that the PSA-2 complex proteins are strong inducers of Th1 immune response in humans (Handman et al 1995 b ;Kemp et al 1998) and protection against virulent challenge in the mouse experimental infection (Handman et al 1995 b). PSA-2 is a family of glycosylinositol phospholipid-anchored polypeptides which are differentially expressed during the parasite life cycle (Handman et al 1995 a ;Jimenez-Ruiz et al 1998) : some members of this family are essentially expressed by Leishmania amastigotes suggesting that they may exert their function during the intercellular stage of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is involved in parasite attachment and invasion of host macrophages via interactions with the complement receptor 3 (CR3) (Kedzierski et al 2004). Previous studies indicated that the PSA-2 complex proteins are strong inducers of Th1 immune response in humans (Handman et al 1995 b ;Kemp et al 1998) and protection against virulent challenge in the mouse experimental infection (Handman et al 1995 b). PSA-2 is a family of glycosylinositol phospholipid-anchored polypeptides which are differentially expressed during the parasite life cycle (Handman et al 1995 a ;Jimenez-Ruiz et al 1998) : some members of this family are essentially expressed by Leishmania amastigotes suggesting that they may exert their function during the intercellular stage of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…CL is often a selfhealing disease; however, persistent lesion lasting for several years is known (nonhealing form). Immune responses to Leishmania have been studied mostly in subjects with active lesions and/or those who had recovered from infection with Old or New World Leishmania parasites (6,(12)(13)(14)(15)24). There are few reports on the immune status of nonhealing patients, particularly those infected with L. major (25).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the key role of cytokines, we were interested in defining the immune response of nonhealing patients and comparing it with that of individuals who had recovered from infection and patients who were newly infected. Immune response to different species of Leishmania have been studied mostly in subjects with active lesions and/or patients who had recovered (6,(12)(13)(14)(15)24). There are few reports on the immune status of nonhealing patients, particularly those infected with L. major.…”
mentioning
confidence: 99%
“…However, immunization with recombinant PSA-2 expressed in L. mexicana promastigotes provided excellent protection against L. major challenge infection [137]. In vitro stimulation of peripheral blood mononuclear cells, from previously exposed cutaneous leishmaniasis patients, with PSA-2 produced high amounts of IFN-γ and TNF-β, and little IL-4, thereby showing a Th1 cytokine pattern [139].…”
Section: Psa-2/gp46/m-2mentioning
confidence: 99%